Improving Science and Social Studies Learning Outcomes Through Project-Based Learning Model Based on Simple Experiments - Aqilla Widyastuti; Abd Rahman Azhari; Roso Sugiyanto; Ichyatul Afrom (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Aim: This study aims to improve science and social studies learning outcomes of third-grade students at SDN 2 Panarung through the implementation of a simple experiment-based Project-Based Learning (PjBL) model that accommodates kinesthetic and hyperactive learning characteristics. Method: The research was conducted using Classroom Action Research with the Kemmis and McTaggart model in two cycles involving 23 third-grade students. Data were collected through learning outcome tests, observations, and documentation, then analyzed descriptively using gain scores and narrative qualitative analysis. Result and Discussions: The findings indicate a significant improvement in student learning outcomes across cycles. The average score increased from 32.17 in the pre-cycle to 56.09 in Cycle I and 87.83 in Cycle II. The N-Gain analysis showed a moderate improvement in Cycle I (0.35) and a high improvement in Cycle II (0.84). Learning mastery also improved from 0% in the pre-cycle to 47.8% in Cycle I and reached 100% in Cycle II. The improvement in Cycle II was supported by the use of simpler and more concrete experiments that aligned with students’ developmental levels and learning styles. Conclusion, The implementation of simple experiment-based PjBL proved effective in enhancing learning outcomes, encouraging active participation, and increasing students’ understanding and motivation. This learning model is recommended for use in classrooms with similar student characteristics.